Nature and consequences of mammalian brain and CSF efflux transporters: four decades of progress - Reynold Spector (2009)
In the last 40 years, especially with the application of new neurochemical and molecular biological techniques, there has been explosive progress in understanding how certain ligands and drugs are transported across the blood-brain barrier and choroid plexus out of brain and CSF. In the CNS, there are several separate efflux transporters with very broad specificity that are responsible for much of the efflux transport. This review focuses on three such transporters: organic acid transporter-3, peptide transporter-2 and P-glycoprotein for which there is substantial new information including 'knockout' models in mice and, in one case, dogs. Moreover, the structural biology and transport mechanism of P-glycoprotein at 3.8 angstroms is described. The overall objective is to show how this new knowledge provides a more thorough understanding (e.g., of molecular mechanisms) of efflux transport and in several cases leads to clinically relevant information that allows better treatment of certain CNS disorders (e.g., meningitis and brain cancer).